New-Onset Status Epilepticus in an 11-year-old Patient with Thyroid Autoimmune Dysfunction: A Case Report of Pediatric Hashimoto Encephalopathy - Costa, Aldo F.; Fernández-Ramos, Joaquín A.; Cazorla, Cristina; López-Laso, Eduardo (Journal of Pediatric Epilepsy, 2024)
Hashimoto encephalopathy (HE) is a neuropsychiatric syndrome associated with positive thyroid antibodies (Ab). Its pathophysiology is still in debate and pediatric cases are considered rare. We present a case of an 11-year-old girl with new-onset refractory status epilepticus (NORSE) who presented a good initial response to corticosteroids but then required a second line of treatment with mycophenolate. In children presenting with NORSE of suspected autoimmune origin and no identification of autoimmune encephalitis traditional Ab, HE must be considered.
Keywords: Hashimoto encephalopathy; thyroid dysfunction; status epilepticus